(3GdMUGQ GdbGSj eCSGJfG aj CaQjbjG (B:s (3hKGFb ef JGQjNfG GdeYGUQ (B/s - (3Ndjd, YeGO GdOjfs ((3HjQhJ (B:s (3eDSSI GdQSGdI ,s, 1988)
(3jQUO gPG GdcJGH eLQjGJ GdUQGY Hjf GdGSdGe h Gdbhi GdeVGOI aj GdSGMI GdGaQjbjI MJi SfI(B1980s
Keywords: (3EaQjbjGs; (3JGQjNs; (3GdESdGes